Recent development of collective Thomson scattering for magnetically confined fusion plasmas. (19th December 2016) - Nielsen, S K; Michelsen, P K; Hansen, S K; Korsholm, S B; Leipold, F; Rasmussen, J; Salewski, M; Schubert, M; Stejner, M; Stober, J; Wagner, D
Abstract: Here we review recent experimental developments within the field of collective Thomson scattering with a focus on the progress made on the devices TEXTOR and ASDEX Upgrade. We discuss recently discovered possibilities and limitations of the diagnostic technique. Diagnostic applications with respect to ion measurements are demonstrated. Examples include measurements of the ion temperature, energetic ion distribution function, and the ion composition.